Corporate Social Responsibility and its Nexus with Firm Performance and Institutional Ownership: An Emerging Market Context - Amna Noor; Muhammad Farooq; Mahwish Yamin; Saleh Nawaz Khan (Journal of Business and Social Review in Emerging Economies, 2020)
Either corporate social responsibility (CSR) is paramount for the firms or not, is a matter of